FRACTURE ANALYSIS AND IMPROVEMENT OF BALL SCREW STEPPED SHAFT - NIE QingFeng; YU DongHui; LI HaiHong (Jixie qiangdu)
The stepped shaft of ball screw was breakaway after loading test of transmission mechanism. To solve this problem,analysis and calculations were carried out from higher hardness,material defect,machining process and experimental loading. The results show that electro discharge machining（ EDM） causes tensile stress and microcosmic cracks on the surface microstructure. Meanwhile,thread corrosion of stepped shaft reduces the loaded area. As a result,torsional fracture of the stepped shaft happened. According to the result,improvement measures including process criterion of EDM control,grinding and polishing are proposed.